2014
DOI: 10.1177/1525740113518342
|View full text |Cite
|
Sign up to set email alerts
|

Role of Importance and Distinctiveness of Semantic Features in People With Aphasia

Abstract: Previous studies suggest that people with aphasia have incomplete lexical-semantic representations with decreased low-importance distinctive (LID) feature knowledge. In addition, decreased LID feature knowledge correlates with ability to discriminate among semantically related words. The current study seeks to replicate and extend previous research that identified patterns of feature knowledge in people with aphasia. Ten adults with aphasia sorted high-, mid-, and low-importance common and distinctive features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
1

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 28 publications
0
7
1
Order By: Relevance
“…For PWA, we observed a role for the provision of distinctive features for adequate description of objects, a feature type that may be particularly difficult to access for some individuals with aphasia (e.g., Mason-Baughman & Wallace, 2014). In addition, it may be that we need to examine these relationships from a more finely grained perspective, both with respect to more discrete feature typeconcept relationships (e.g., fruit: visual-perceptual color, animal: visual-perceptual form) and across performance of persons with aphasia with different lesion profiles (e.g., Gainotti, 2006; see also Antonucci, 2014aAntonucci, , 2014b.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…For PWA, we observed a role for the provision of distinctive features for adequate description of objects, a feature type that may be particularly difficult to access for some individuals with aphasia (e.g., Mason-Baughman & Wallace, 2014). In addition, it may be that we need to examine these relationships from a more finely grained perspective, both with respect to more discrete feature typeconcept relationships (e.g., fruit: visual-perceptual color, animal: visual-perceptual form) and across performance of persons with aphasia with different lesion profiles (e.g., Gainotti, 2006; see also Antonucci, 2014aAntonucci, , 2014b.…”
Section: Discussionmentioning
confidence: 96%
“…A relatively small body of evidence has begun to amass examining performance of persons with aphasia (PWA) in comprehensionand production-based semantic feature tasks. One robust finding is that difficulty processing distinctive feature knowledge is linked both to the ability to distinguish among semantically related concepts and to word retrieval (MasonBaughman & Wallace, 2013, 2014Wallace & MasonBaughman, 2012). Work in our own lab with PWA further highlights the importance of distinctive feature cues for accurately verifying concept-feature relationships as well as their importance in sufficiently describing objects such that a communication partner would be likely to identify the item being described in the absence of its label (Antonucci, 2014a(Antonucci, , 2014b.…”
mentioning
confidence: 99%
“…While these previous studies suggest that semantic knowledge is preserved in PWA, several researchers have demonstrated impairments in accessing certain types of features (Antonucci, 2014; Marques et al, 2013; Mason-Baughman & Wallace, 2014; Thompson & Jefferies, 2013). Researchers who have examined semantic access in aphasia have demonstrated that PWA may present with deregulation in a single modality (Thompson & Jefferies, 2013), superordinate categorical deficits (Marques et al, 2013), and feature processing differences (Antonucci, 2014; Mason-Baughman & Wallace, 2014).…”
mentioning
confidence: 90%
“…Researchers classify features in a number of different ways. Mason-Baughman and Wallace (2014) classified features based on how distinctive the features were in identifying concepts. Features that are generally associated with only one concept (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation